Status of Salivary Nitric Oxide Levels and Buccal Epithelial Cell DNA Damage in Potentially Malignant Disorders – A Biochemical Study - KA, Fazil; Castelino, Renita Lorina; Babu, Subhas Gogineni; Madi, Medhini; Shetty, Shishir Ram; Balan, Preethi; Bhat, Supriya (Journal of Dentistry Indonesia, 2017)
Oral cancer is a progressive, multistage disease in which changes in genetic structure and cellular morphology occur from the normal to the premalignant state and then to the malignant state. Nitric oxide (NO.) is an uncharged molecule with an unpaired electron. It is highly reactive and interacts with DNA molecules, resulting in DNA damage. Objective: To evaluate the salivary nitric oxide levels and buccal epithelial cell DNA damage in patients with potentially malignant oral disorders. Methods: The salivary nitric oxide levels and buccal epithelial cell DNA damage were estimated in 20 healthy individuals without oral lesions, in 20 subjects having smoking and/or tobacco chewing habits without oral lesions, and 20 patients with a potentially malignant oral disorder. Results: The salivary nitric oxide levels were significantly greater in the subjects with tobacco chewing and/or smoking habits without oral lesions than in the healthy controls. Similarly, the extent of DNA damage was higher in the subjects with potentially malignant disorders and in the subjects with tobacco chewing and/or smoking habits without oral lesions than in the healthy controls. Conclusion: The encouraging results of the present study indicated the potential involvement of nitric oxide in the pathogenesis of potentially malignant oral disorders.